Hepatocellular Carcinoma with Both Fibrolamellar and Classical Components: An Unusual Morphological Pattern - Diana Castro-Villabón; Luis E. Barrera-Herrera; Paula A. Rodríguez-Urrego; Rachel Hudacko; Alonso Vera; Johanna Álvarez; Rafael Andrade; Rocío López (Hindawi Limited, 2015)
Fibrolamellar carcinoma (FLC) is an uncommon form of primary liver malignancy with unique clinical, histological, and biological characteristics. It is usually seen in young adults without underlying liver disease. Histologically, it shows large cells with abundant eosinophilic cytoplasm, large vesicular nuclei, prominent nucleoli, and lamellar type fibrosis. In contrast, classical hepatocellular carcinoma (HCC) is typically present in elderly male patients with cirrhosis. It is the most common histological subtype, and it is characterized by its resemblance to the normal liver, both in its growth pattern and its cytology. The unusual case of a liver carcinoma that presented with histological features of both FLC and classical HCC is herein reported. This was the case of a 37-year-old female complaining of diffuse abdominal discomfort and epigastric pain for two months. She was referred to us for further management after she was diagnosed with HCC in a noncirrhotic liver. She underwent a left-sided hepatectomy. A yellow nodular mass with well-defined borders and a necrotic center was present in the resection specimen. The morphological features and immunohistochemical studies were consistent with a diagnosis of FLC mixed with classical HCC. The patient was followed up for five months, and no signs of recurrence were evident.